IL1-blocking therapy in colchicine-resistant familial Mediterranean fever - Köhler, Birgit; Lorenz, Hanns-Martin; Blank, Norbert (European Journal of Rheumatology, 2018)
Approximately 10%-20% of patients with familial Mediterranean fever (FMF) show an inadequate response to colchicine. In our cohort study, patients with FMF with or without amyloidosis and with an inadequate response to colchicine were treated with anakinra or canakinumab.
Die angegeben DOI ist nicht mit dem Artikel verlinkt
Gesehen am 06.12.2019